Pendugaan Penambatan Karbon Kelapa Sawit (Elaeis Guineensis Jacq) Umur 15 Tahun pada Lahan Gambut di PT. Waimusi Agroindah Afdeling XII Kebun Sepucuk, Kecamatan Pedamaran Timur, Kabupaten Ogan Komering Ilir - Wulandari, Anisa; Prayitno, Muh Bambang (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Wulandari, A., & Prayitno, M.B. (2024). Estimation of 15-Year-Old Oil Palm (Elaeis Guineensis Jacq) Carbon Sequestration on Peatland at PT Waimusi Agroindah Afdeling XII, Kebun Sebubuk, Pedamaran Timur District, Ogan Komering Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 556–562). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One significant carbon storage area is in plant stands, which can be measured through plant biomass. The amount of carbon stored depends on the diversity and density of plants in an area, the type of soil present, and how it is managed. This research was carried out on oil palm plants on peatlands at PT Waimusi Agroindah, located in Afdeling XII, Kebun Sepucuk, East Pedamaran District, Ogan Komering Ilir Regency, South Sumatra, from September to October 2023. Estimating carbon tethering using carbon using the Non-destruction method by measuring the diameter of the rod with the formula W = 0.1208 and estimating plant carbon tethering. Measurements are made by measuring the diameter of the rod using a modification tool to measure the diameter of the rod. Samples were taken 3 different plots and with different areas but still in the same plant age, samples were taken as many as 18 points on each plot with the number of samples obtained as many as 54 samples. For oil palm plants, each plot with a plant age of 15 years has a diameter that is not too different. The results showed that oil palm plants with the highest average biomass value were found in plot 1 with a total carbon absorption of 21,338.75 tons . Samples were taken in 3 different plots and with different areas but still in the same plant age, samples were taken as many as 18 points on each plot with the number of samples obtained as many as 54 samples. It is suspected that the biomass of carbon reserves and the amount of carbon tethering of oil palm plants planted on peatland at the plant age level is 15 years. For oil palm plants, each plot with a plant age of 15 years has a diameter that is not too different. The results of the study showed that oil palm plants with the highest average biomass value were found in plot 1 with a total carbon sequestration of 21,338.75 tons.